Leverage : how to get it and how to keep it in any negotiation - Volkema, Roger J. (AMACOM, 2006)
The most important aspect of any negotiation is the real or imagined advantage one holds in a given situation. The concept of "leverage" can refer to time, money, reputation, or any other factor deemed important by one of the two parties - but whatever it refers to, the ability to recognise and use this often-hidden trump card is what makes a master negotiator. "Leverage" is an interactive, practical book that shows readers how to improve their negotiation skills and use leverage to get whatever they want out of any situation